Safety and Tolerability of Strength Training in Spinal and Bulbar Muscular Atrophy: A Case Report - Vincent Shieh; Cris Zampieri; Paul Stout; Galen O. Joe; Angela Kokkinis; Kenneth H. Fischbeck; Christopher Grunseich; Joseph A. Shrader (Journal of Rehabilitation Medicine - Clinical Communications, 2022)
Objective: Spinal and bulbar muscular atrophy is characterized by slow-progressive muscle weakness, decreased functional performance and falls. Research into the use of exercise in spinal and bulbar muscular atrophy has shown equivocal to negative results, although authors suggest that patients with spinal and bulbar muscular atrophy may benefit from both increased exercise intensity and shorter bout duration. The aim of this case report is to explore the safety of a moderate-intensity strength training programme coupled with dynamic balance and function-specific training in a patient with spinal and bulbar muscular atrophy. Case report: A 56-year-old man with spinal and bulbar muscular atrophy presented with multiple falls and declining performance in physical, vocational, and recreational activities. Examination revealed several musculoskeletal impairments that were sub-clinical to mild compared with an SBMA natural history cohort. Intervention and outcome: A 15-week moderate-intensity exercise programme combining weightlifting and functional exercises was performed under clinical supervision. Exercise volume, frequency and intensity were adjusted based on patient-reported outcomes and muscle damage blood markers. Performance-based and selfreported functional improvements occurred that exceeded the minimal clinically important difference. The intervention was well tolerated and the patient nearly doubled his baseline 10-repetition maximums for weight-lifting exercises. Conclusion: Exercise therapy combining weightlifting and upright functional training led to meaningful performance improvements in this case of a patient with spinal and bulbar muscular atrophy and relatively low disease burden.